The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1139/cjm-47-3-237
|View full text |Cite
|
Sign up to set email alerts
|

Intact soil-core microcosms compared with multi-site field releases for pre-release testing of microbes in diverse soils and climates

Abstract: Intact soil-core microcosms were used to compare persistence of Pseudomonas chlororaphis 3732RN-L11 in fallow soil and on wheat roots with field releases at diverse sites. Parallel field and microcosm releases at four sites in 1996 were repeated with addition of one site in 1997. Microcosms were obtained fresh and maintained at 60% soil water holding capacity in a growth chamber at 70% relative humidity, a 12-hour photoperiod, and constant temperature. Persistence of 3732RN-L11 was measured at each site in fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…kurstaki HD-1 crystalline protein gene into strains of Pseudomonas fl uorescens (Obukowicz et al 1986 ) . Limited fi eld releases of these live microorganisms occurred, though only with strain variants engineered with reporter genes (Kleupfel et al 1991 ;Angle et al 1995 ;Gagliardi et al 2001 ) . EPA questioned the safety of pseudomonads expressing B.t.…”
Section: Historical Regulatory Perspectivementioning
confidence: 97%
“…kurstaki HD-1 crystalline protein gene into strains of Pseudomonas fl uorescens (Obukowicz et al 1986 ) . Limited fi eld releases of these live microorganisms occurred, though only with strain variants engineered with reporter genes (Kleupfel et al 1991 ;Angle et al 1995 ;Gagliardi et al 2001 ) . EPA questioned the safety of pseudomonads expressing B.t.…”
Section: Historical Regulatory Perspectivementioning
confidence: 97%
“…Microcosms were constructed of 5-cm inner diameter schedule 40 polyvinyl chloride (PVC) plumbing pipe, 17.5 cm long, and ¢lled with ¢eld soil as described previously [7]. Microcosms were placed in a greenhouse and watered when necessary to maintain 60% saturation.…”
Section: Methodsmentioning
confidence: 99%
“…One would not expect this feature in any member of that cluster of species. This observation has even been used as a basis for introducing a lac zy marker gene into one such micro-organism as a means of tracing movement in the environment (Gagliardi et al, 2001) since no Pseudomonas found naturally occuring at a release site for this GMM should have that feature and thus be confused with the GMM .…”
Section: Limits To the Ability To Assign Names To Some Taxamentioning
confidence: 99%
“…Such issues as toxin production or pathogenicity potential are obvious ones for evaluation. Other examples of data may include experience with field releases under controlled conditions or microcosm studies (e.g., Gagliardi et al, 2001) for strains related to the subject organism.…”
Section: Relevance Of Comparison Organismsmentioning
confidence: 99%
See 1 more Smart Citation